2021
DOI: 10.1108/ict-12-2020-0114
|View full text |Cite
|
Sign up to set email alerts
|

The curvilinear relationship between servant leadership and work-family conflict: the moderating role of age in Chinese female workers

Abstract: Purpose Building on social exchange theory and selection, optimization and compensation theory, this study aims to examine a moderated curvilinear relationship between servant leadership (SL) and work-family conflict (WFC). Design/methodology/approach Participants were 329 female workers recruited from a Chinese small business in the service Industry. A three-step hierarchical regression was conducted to examine the relationships among the variables and the incremental contribution of SL and age and the squa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 87 publications
0
2
0
1
Order By: Relevance
“…This result coincides with some previous studies (Wang et al , 2017; Tang et al , 2016) as these studies revealed that there is a positive link between servant leadership and work–life balance. Also, according to Tang et al (2016), Wang et al (2017) and Xie et al (2021), servant leadership is a supportive factor for the family well-being of family employees.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This result coincides with some previous studies (Wang et al , 2017; Tang et al , 2016) as these studies revealed that there is a positive link between servant leadership and work–life balance. Also, according to Tang et al (2016), Wang et al (2017) and Xie et al (2021), servant leadership is a supportive factor for the family well-being of family employees.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This positive workplace effect also extends to their personal lives, helping to reduce work-family and family-work conflicts (Wang et al, 2017;Winston, 2022). SL contributes to spouse-family satisfaction through job-social support (Rofcanin et al, 2021;Xie et al, 2021;Yang et al, 2018). In addition, SL promotes goal attainment and a sense of meaning in life for individuals (Chughtai, 2018;Devi, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…En ese sentido, la literatura académica indica que la edad y la satisfacción laboral se correlacionan positiva y signicativamente con el capital psicológico (Agnihotri & Bhattacharya, 2020;Mvana & Louw, 2020;Paul & Phua, 2011;Prasad & Sandhyavani, 2019). Sin embargo, en el caso del liderazgo de servicio no se ha reportado asociación (Xie et al, 2021). En la tabla 5 se muestran los resultados de la validez nomológica y como en ella se aprecia, los resultados de este trabajo coinciden con los antecedentes teóricos disponibles, lo que evidencia el modelo de medición tiene validez nomológica.…”
Section: Tablaunclassified